2015
DOI: 10.3393/ac.2015.31.5.176
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features and Predictive Risk Factors for Reoperation in Patients With Perianal Crohn Diseases; A Multi-Center Study of a Korean Inflammatory Bowel Disease Study Group

Abstract: PurposePerianal lesions are common in Crohn disease, but their clinical course is unpredictable. Nevertheless, predicting the clinical course after surgery for perianal Crohn disease (PCD) is important because repeated operations may decrease patient's quality of life. The aim of this study was to predict the risk of reoperation in patients with PCD.MethodsFrom September 1994 to February 2010, 377 patients with PCD were recruited in twelve major tertiary university-affiliated hospitals and two specialized colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Respondents widely rejected the use of cutting setons in this group of patients. Patients with pCD tend to a chronic and recurrent disease course necessitating multiple interventions, and therefore efforts should be made to preserve continence where possible . The conservative advice given to less experienced surgeons suggests that UK practice is aimed at avoiding iatrogenic exacerbation of fistulating disease and tends to favour management by experienced colorectal surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents widely rejected the use of cutting setons in this group of patients. Patients with pCD tend to a chronic and recurrent disease course necessitating multiple interventions, and therefore efforts should be made to preserve continence where possible . The conservative advice given to less experienced surgeons suggests that UK practice is aimed at avoiding iatrogenic exacerbation of fistulating disease and tends to favour management by experienced colorectal surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…There are a wide range of procedures offered as definitive surgical options for patients with pCD. Draining seton alone, fistulotomy, fistula plug and LIFT have been described in the literature, with varying outcomes, although this is mostly on the basis of observational and not trial‐based data . The variety of choice in definitive surgery may reflect in part a lack of consensus and limited evidence for the surgical management of pCD, but may also be influenced by the expertise of individual surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…9 The currently available strategy for treating PCD includes seton placement which can prevent the formation of recurrent abscess and preserve the function of the anal sphincter, as well as medical treatment with antitumor necrosis factor (TNF) agents. [10][11][12] However, fistula still recurs in 22%-28% of the patients, 11,13 and the 5-year cumulative rate of reoperation is approximately 40%. 13,14 There have been several reports on possible risk factors for the recurrence of PCD, 13,15 although there is a lack of clarity regarding the optimal medical treatment after surgery and the risk of reoperation.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, fistula still recurs in 22%-28% of the patients, 11,13 and the 5-year cumulative rate of reoperation is approximately 40%. 13,14 There have been several reports on possible risk factors for the recurrence of PCD, 13,15 although there is a lack of clarity regarding the optimal medical treatment after surgery and the risk of reoperation. Therefore, in the current study we aimed to identify risk factors that may be used to predict reoperation due to the recurrence of perianal fistula in Korean patients with CD.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective study reported the cumulative risks of reoperation for patients operated on for PCD, as well as the related risk factors [ 1 ]. According to the study, the risk of reoperation increases during the disease's course, reaching up to 50% after the first surgical treatment, and risk factors associated with reoperation are a young age at the onset of CD, a history of abdominal surgery for CD, and the type of surgery.…”
mentioning
confidence: 99%